Side effects can enhance treatment response through expectancy effects: an experimental analgesic randomized controlled trial. Issue 6 (June 2017) - Berna, Chantal; Kirsch, Irving; Zion, Sean R.; Lee, Yvonne C.; Jensen, Karin B.; Sadler, Pamela; Kaptchuk, Ted J.; Edwards, Robert R.
Abstract : Abstract: In randomized controlled trials, medication side effects may lead to beliefs that one is receiving the active intervention and enhance active treatment responses, thereby increasing drug–placebo differences. We tested these hypotheses with an experimental double-blind randomized controlled trial of a nonsteroidal anti-inflammatory drug with and without the addition of atropine to induce side effects. One hundred healthy volunteers were told they would be randomized to either combined analgesics that might produce dry mouth or inert placebos. In reality, they were randomized double blind, double-dummy to 1 of the 4 conditions: (1) 100 mg diclofenac + 1.2 mg atropine, (2) placebo + 1.2 mg atropine, (3) 100 mg diclofenac + placebo, or (4) placebo + placebo, and tested with heat-induced pain. Groups did not differ significantly in demographics, temperature producing moderate pain, state anxiety, or depression. Analgesia was observed in all groups; there was a significant interaction between diclofenac and atropine, without main effects. Diclofenac alone was not better than double-placebo. The addition of atropine increased pain relief more than 3-fold among participants given diclofenac ( d = 0.77), but did not enhance the response to placebo ( d = 0.09). A chain of mediation analysis demonstrated that the addition of atropine increased dry mouth symptoms, which increased beliefs that one had received the active medication, which, in turn, increased analgesia. In addition to this indirect effect of atropine on analgesia (via dry mouth and beliefs), analyses suggest that among those who received diclofenac, atropine directly increased analgesia. This possible synergistic effect between diclofenac and atropine might warrant future research. Abstract : Supplemental Digital Content is Available in the Text.The experience of induced side effects can increase beliefs to be on active medication, enhancing pain relief in participants treated with NSAIDs in an RCT model.